2006
DOI: 10.1080/09541440500334466
|View full text |Cite
|
Sign up to set email alerts
|

On the emergence of the discriminative mode for transitive-inference

Abstract: Transitive-inference tasks play increasing roles in many areas of cognitive science. However, discrepancies between the two competing paradigms (classical-Piagetian and IP-paradigm) imply that one paradigm fails to index its target (deductive) competence. Here, potential flaws of one were addressed using considerations from the other. Children of 5 Á7 years (N 0/216) solved 3-term transitive problems, some implying a single largest item, and some not. Findings indicate a discriminative competence (a Transitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 43 publications
(130 reference statements)
1
23
1
Order By: Relevance
“…A similar test for 5 year-olds showed that they were reliably above chance (t (65) = 3.566, p = 0.001), as were the 6 year-olds (t (82) = 9.119, p < 0.001). Wright (2006a) suggests that the notion of a competence threshold might be useful in developmental research on transitive reasoning. Borrowing the concept from general psychophysical designs, he asserted that the competence threshold should be defined as that level laying as close to perfect performance as it is to chance performance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A similar test for 5 year-olds showed that they were reliably above chance (t (65) = 3.566, p = 0.001), as were the 6 year-olds (t (82) = 9.119, p < 0.001). Wright (2006a) suggests that the notion of a competence threshold might be useful in developmental research on transitive reasoning. Borrowing the concept from general psychophysical designs, he asserted that the competence threshold should be defined as that level laying as close to perfect performance as it is to chance performance.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in close agreement with three-term studies (e.g., Markovits & Dumas, 1999; cf. Oakhill, 1984;Wright, 2006a).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations